Website-based e-counseling model for academic services in higher education: a feasibility and effectiveness analysis - Amanah, Siti; Amalianita, Berru; Santoso, Ridwan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study aimed to develop and examine the feasibility and effectiveness of a website-based e-counselling model as a support service for academic services in higher education. The increasing need for flexible, accessible, and efficient counselling services motivated the development of this model, particularly to assist students in coping with academic challenges and adapting to the university environment. The study employed a research and development approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The feasibility of the model was evaluated through expert validation and user testing, with indicators including content relevance, system usability, service accessibility, and functional design. The results of expert validation indicated that the website-based e-counselling model was categorized as highly feasible for implementation. User testing further supported these findings, with the overall feasibility assessment classified as very feasible. The effectiveness of the model was tested using a one-group pre-test–post-test design without a control group. Effectiveness indicators included students’ perceived quality of academic services, accessibility of counselling services, responsiveness of academic support, and student satisfaction with counselling services. Statistical analysis using a paired-sample t-test revealed a significant improvement in post-test scores compared to pre-test scores (p < 0.001). The magnitude of the improvement was substantial, as indicated by a large effect size (Cohen’s d = 0.94). These findings demonstrate that the developed website-based e-counselling model is not only feasible but also highly effective in enhancing the quality of academic services for university students.